P99. Predictors of new cerebral microbleeds in patients with antiplatelet drug therapy. Issue 8 (August 2015) - Menzler, K.; Hausdörfer, M.; Mayer, C.; Belke, M.; Gerstner, A.; Teepker, M.; Werner, R.; Hamer, H.; Oertel, W.; Rosenow, F.; Knake, S.
<x xml:space="preserve">Abstract</x> Background Cerebral microbleeds (CMBs) are an MRI marker of vascular damage in the brain and are associated with an increased risk for ischemic and especially hemorrhagic stroke. CMBs are known to be more prevalent in patients who take antiplatelet drug therapy, which is commonly used for secondary prevention in patients with ischemic stroke. The aim of the present study was to evaluate the usefulness of susceptibility weighted imaging (SWI) to identify patients at high risk for the development of new CMBs under antiplatelet drug therapy. Methods We examined 58 patients with a first ischemic stroke or transitory ischemic attack (TIA) in whom a secondary prevention with an antiplatelet drug therapy was initiated. In the first week after the onset of stroke a 3T MRI including a susceptibility weighted imaging (SWI) sequence was performed. 40 patients were available for follow-up MRI after 6 months. The association of baseline CMBs with presence and number of new CMBs at follow-up was investigated using stepwise logistic regression and Spearman's correlation coefficient. Also, the association of cardiovascular risk factors and stroke etiology with the presence and number of CMBs at baseline and follow-up was analysed using the same statistical methods. Results When including only the patients with CMBs at baseline, there was a significant association between the number of CMBs at baseline and the number of new CMBs. This association was not present when including all patients. At follow-up the presence and number of CMBs was significantly associated with hyperlipidemia. At this stage there was a significant correlation between the number of CMBs and atherothrombotic stroke. The number of new CMBs was significantly associated with the cardiovascular risk factors male sex and age >70 years. It also correlated significantly with atherothrombotic stroke. Conclusions Risk factors associated with the presence of or number of new CMBs when taking antiplatelet therapy included several known cardiovascular risk factors like hyperlipidemia, male sex and age >70 years. Also, atherothrombotic stroke was significantly associated with the presence or number of new CMBs. The number of CMBs in the SWI sequence was only associated to the number of new CMBs when patients without CMBs were excluded. It might therefore only be helpful in patients who already show CMBs before taking antiplatelet drug therapy.